Impacts of Tibetan Plateau sensible heat and El Niño–Southern Oscillation on precipitation over South China under the background of the PDO - Sun, Yang; Shan, Xing; Zhou, Shunwu; Wang, Meirong; Wang, Chuanhui; Deng, Zhongren (Frontiers in Environmental Science, 2023)
This study aims to investigate the impacts of the spring sensible heat (SH) over the Tibetan Plateau (TP) and the El Niño–Southern Oscillation (ENSO) in the preceding wintertime on midsummer (July–August) precipitation over South China under the different Pacific decadal oscillation (PDO) phases. More specifically, eight classifications are adopted at the demarcation point around 1996 when the spring SH over the TP and the midsummer precipitation in South China occurred as well as the PDO phase transition, including positive and negative SHs and ENSOs under a positive PDO phase (1979–1996) and a negative PDO phase (1997–2019), respectively, based on the Niño-3 index and the spring SH calculated from 48 stations over the central and eastern parts of the TP. The results show that both the spring SH and the ENSO in preceding wintertime have a significant impact on the midsummer precipitation over South China; that is, when the two factors are in their respective positive (negative) phase, the midsummer precipitation in South China is generally less (more). Importantly, the phase change of background field PDO can significantly enhance the effect of the SH and the ENSO on summer precipitation over South China. Moreover, compared with the preceding wintertime ENSO, the spring SH over the TP contributes more to the midsummer precipitation in South China based on analyses of their independent and synergistic effects. The main mechanism responsible for the anomalous midsummer precipitation over South China are the combined effects of the South Asian high (SAH) and the western Pacific subtropical high (WPSH), which are controlled by the spring SH anomaly over the TP and the ENSO, respectively. Deep understanding of the dominant factors of the midsummer precipitation over South China will help understand the local climate change and reduce the losses caused by drought and flood disasters.